(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2025)
The physical-chemical characteristics of medicinal plants are well-known as is their abundance in natural medications from several molecular classes, including phenolic compounds, tannins, coumarins, and flavonoids, which provide efficient defense against a wide range of diseases. Oleanderum is widely used in medicine. It has a wide range of biological properties, such as the ability to treat eye and skin ailments and to be cardiotonic, anti-inflammatory, antibacterial, anticancer, cytotoxic and antiplatelet aggregation diuretic. The goal of the current investigation was to assess the antiradical scavenging and phytochemical screening properties of several N. oleander leaves extracts. Numerous bioactive compounds, including saponins, phenolics, cardiac glycosides, alkaloids, tannins, flavonoids, terpenoids, protein and carbohydrates were found in all of the oleanderum extracts according to phytochemical analyses, while quinones are absent in all the extracts and mucilage/gums are also absent in all extract except n-hexane. According to the results of antiradical scavenging activity its extract has antioxidant properties in the DPPH assay ranging from (% inhibition 4.7±1.2-85±5.4) which is higher than standard antioxidant BHT (% inhibition 20-54 and reducing power activity (absorbance 0.15-1.8),) that was higher than BHT (absorbance 0.12-1.020) at concentrations of 10-50 μg/ml. According to the research, oleanderum leaves exhibit a variety of phyto-pharmacological properties. By applying cutting-edge extraction technology and novel biotechnology approaches, these leaves may be used to treat a range of illnesses. Bangladesh J. Sci. Ind. Res. 60(2), 107-114, 2025